Determination of Blood Micromineral and Fat-Soluble Vitamin Values for White-tailed Deer. (7th May 2021) - Greenwood, Megan P; Kelley, Stanley F; Beverly, Marcy M; Urso, Phil; Anderson, Mark
Abstract: The current National Academies of Sciences, Engineering, and Medicine (NASEM) for trace mineral and vitamin requirements for cervids are based on data collected from various small ruminant species. Lack of baseline requirements make diet formulation for high fenced, white-tailed deer ( Odocoileis virginianus ) herds particularly ambiguous. This study was to determine a baseline value for whole blood and serum micromineral and vitamin concentrations for white-tailed deer in an attempt to establish dietary requirements of trace minerals and vitamins. Open does (n = 226) were sampled using jugular venipuncture during fall breeding procedures. Captive-raised does housed at various high fenced ranches (n = 3) throughout Texas were used, each with unique management strategies. Blood samples were analyzed for micromineral levels (Co, Cu, Fe, Mn, Mo, Se, and Zn) and fat-soluble metabolites (vitamin A, vitamin E, and cholesterol). Age of the doe and ranch were used as main effects using the GLM procedure in. Sampled averages across all ranches were 6.26 ng/mL of Co, 1.05 µg/mL of Cu, 219.47 µg/mL of Fe, 4.40 ng/mL of Mn, 4.23 ng/mL of Mo, 172.32 ng/mL of Se, 0.54 µg/mL of Zn, 286.76 ng/mL of vitamin A, 1.80 µg/mL of vitamin E, and 79.27 of cholesterol. Micronutrient levels were not affected by age; however, least squared differences existed between the main effect ranch for Co (P < 0.01), Cu (P < 0.01), Fe (P < 0.01), Mo (P < 0.01), Mn (P < 0.01), Se (P < 0.01), Zn (P < 0.01), vitamin E (P < 0.01), and cholesterol (P = 0.038) in serum. There was an observed interaction of age and ranch for vitamin A (P = 0.038). Factors such as feed, forage, soil, genetics, and health management protocols could explain the broad range in values. The establishment of circulating blood micronutrient levels will serve as a baseline for future white-tailed deer nutrient requirement research and feed formulation.